IMF Survey, Volume 35, Issue 06. (IMF Survey; IMF Survey ;, 2006)
MD meets SSA leaders; ART. IV: Belgium, Ecuador, Finland, Nepal; U.K. policy frameworks; Ghana: quasi-fiscal activities; Africa and Doha Round; euro area product markets; ASI: FDI; prescriptions for financial stability.